PKM Digital Literacy to Improve Ethics and Digital Security for SMKS PGRI 3 Denpasar Students - Ni Luh PNSP Astawa; Ni Kadek Sri Mas Dwayani; I Komang Suartama (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
This article is based on the Community Partnership Program (PKM) which seeks to increase digital literacy knowledge for students. This knowledge is an asset to have the ability to sort and evaluate digital media content sharply and thoroughly. It is hoped that this knowledge will enable students to utilize information according to their needs. The method used is lectures to explain material related to digital literacy and the practice of applying several digital security methods to the WhatsApp application. Discussions were also held with students regarding material or experiences regarding digital literacy that they had. The target of the activity was 70 students of SMKS PGRI 3 Denpasar. The results of this activity indicate an increase in knowledge about digital literacy. This increase can be seen from the comparison of the pre-test and post-test results of 1.9.